Rock art of south-eastern South Africa and Lesotho, 1806 to 1997: an annotated bibliography - Herbert, K. (Southern African Humanities, 2021)
An annotated bibliography on the rich rock art (including paintings and engravings) of the south-eastern area of South Africa (including KwaZulu-Natal, the Drakensberg mountains, East Griqualand, Barkly East and the eastern Free State) and Lesotho, covering the literature from 1806 - 1997, is presented. The south-eastern mountain area in particular, has a large number of known paintings. Mazel (1984a) reports on 20 668 paintings in the KwaZulu-Natal Drakensberg. Smits (1992b) reports on 700 rock painting sites, and Van Rijssen (1985) mentions 15 000 paintings recorded by the ARAL (Analysis of Rock Art in Lesotho) project. This bibliography includes 925 references and records 531 entries for the period 1981 - 1997. It also incorporates a revised version of the first bibliography on the the rock art of KwaZulu-Natal and Lesotho compiled by Cherry (1982). Some 152 entries of the 286 in the original bibliography were amended or added to and 108 new pre-1981 references were also added. In the annotations, 168 additional references to reviews and comments on the references listed are found. To cite this article: Herbert, K. 1998. Rock art of south-eastern South Africa and Lesotho, 1806 to 1997: an annotated bibliography. Natal Museum Journal of Humanities 10: 33-149.